2001
DOI: 10.1037/h0089455
|View full text |Cite
|
Sign up to set email alerts
|

Attachment style, emotional control, and breast cancer.

Abstract: Research in emotional control and interpersonal relations and health suggest possible linkages between attachment theory and cancer. The suppression of negative emotions, characteristicof avoidant attachment, is considered to be the core of the Type C pattern. Women with breast cancer (n=52) and without cancer (n=52) were assessed regarding attachment style and emotional control. It was hypothesized that the cancer group would score significantly higher on avoidant attachment and emotional control than the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 16 publications
0
15
1
1
Order By: Relevance
“…Previous applications of attachment theory in women with breast cancer have tried to identify attachment styles that characterize the group as a whole [54,55]. However, the present findings indicate the need to understand variations within this population.…”
Section: Research and Clinical Implicationscontrasting
confidence: 65%
“…Previous applications of attachment theory in women with breast cancer have tried to identify attachment styles that characterize the group as a whole [54,55]. However, the present findings indicate the need to understand variations within this population.…”
Section: Research and Clinical Implicationscontrasting
confidence: 65%
“…It is thus likely that anxious tendencies will be linked with a tendency to be critical towards the partner in the situation of breast cancer (Maunder, Lancee, Nolan, Hunter, & Tannenbaum, ; Mikulincer & Shaver, , ). To date, the few studies that have assessed the impact of attachment in breast cancer have shown that women with anxious or avoidant tendencies have lower psychological adaptation indexes to the stress of the disease (Favez et al ., ; Rodin et al ., ; Tacón, Caldera, & Bell, ).…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional and longitudinal studies reported that individuals who described their parents as less close, loving and protective were at higher risk of developing cancer [1618]. In accordance, women with breast cancer obtained significantly higher scores on avoidant attachment and emotional control compared to healthy women [19]. …”
Section: Introductionmentioning
confidence: 99%